2015
DOI: 10.1111/liv.12990
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of DASH diet on weight loss and metabolic status in adults with non‐alcoholic fatty liver disease: a randomized clinical trial

Abstract: Consumption of DASH diet for 8 weeks among patients with NAFLD had beneficial effects on weight, BMI, ALT, ALP, triglycerides, markers of insulin metabolism, inflammatory markers, GSH and MDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
196
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(228 citation statements)
references
References 45 publications
8
196
2
5
Order By: Relevance
“…NAFLD is defined as a systemic, multifactorial disease involving multiple organs, such as adipose tissue, muscle, and intestines [39]. The underlying mechanism for the development and progression of NAFLD is complex and multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is defined as a systemic, multifactorial disease involving multiple organs, such as adipose tissue, muscle, and intestines [39]. The underlying mechanism for the development and progression of NAFLD is complex and multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…Initial and followup ultrasounds showed that more patients in the DASH diet group (80% compared with 43.3%, P = 0.003) had a decreased NAFLD grade by ultrasound (53). Patients in the DASH diet group also had more significant decreases in their BMI, insulin and ALT concentrations, serum TGs, and totalto-HDL cholesterol ratio (53). This suggests that caloric restriction alone may be inadequate and that diet type may be more important in improving liver enzymes and hepatic steatosis.…”
mentioning
confidence: 97%
“…In a randomized controlled trial, 60 NAFLD subjects (diagnosed by ultrasound and elevated liver enzymes) were randomly assigned to either the DASH diet or control diet for 8 wk (53). DASH is a sodium-restricted (<2400 mg/d) diet rich in vegetables, fruits, whole grains, and low-fat dairy, and low in saturated fats, cholesterol, refined grains, and sweets.…”
mentioning
confidence: 99%
See 2 more Smart Citations